PROBLEMS OF INTEGRATION OF THE HIGH ORDER STRATEGY AT THE AFFILIATED COMPANY AT M&A - Opanasyuk, V.V.; Zborovsky, A.V. (The actual problems of regional economy development, 2017)
The article is dedicated to studying the problems of integration of higher-ranking strategies and to affiliated company for merger and acquisition transactions. The elements of the company's strategy with expansion into the foreign market are considered. The main goals of the conclusion of M & A transactions are determined, their distribution is indicated, the buyer’s goals are considered separately. The advantages and results of conclusions of various horizontal and vertical M & A transactions, the efficiency of transactions in the long-term and short-term periods are investigated. The performance indicators of international M & A are detected. Risks in concluding M & A transactions are grouped, the strategies, methods and tools of financial risks’ managing are well-grounded . The recommendations of checking and ensuring the purity of the M & A agreement are given. Further research should be directed at developing measures and mechanisms of implementing the higher-ranking strategy in the affiliated company when implementation M & A.